2017
DOI: 10.1002/jbm.a.35962
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/nHAC/PLGA microsphere vehicle for sustained release of rhBMP‐2 and its derived synthetic oligopeptide for bone regeneration

Abstract: Both of the osteogenic factor and the suitable delivery system in bone tissue engineering are essential for bone regeneration. In this study, we manufactured two kinds of composite vehicles for sustained release of rhBMP-2 and its derived synthetic oligopeptide (Peptide-24, abbreviated as P24) for osteogenesis and bone defect repair. The composite vehicle was based on cross-linked chitosan, nano-hydroxyapatite/collagen (nHAC), and poly (lactide-co-glycolide) acid microsphere. The physicochemical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Autogenous transplantation, the gold standard method for bone therapy, is limited for the lack of sources of autografts [ 7 , 8 ], besides it also has a risk of infection, nerve damage and other postoperative complications [ 9 ]. To address these challenges, researchers have focused on the development of novel biomaterials with potential in tissue engineering and regeneration to facilitate bone regeneration [ [10] , [11] , [12] , [13] ]. Among synthetic biomaterials, hydrogels consisting of natural or synthetic polymers that exhibit excellent mechanical properties and biocompatibility are ideal scaffolds to emulate extracellular matrices for cell proliferation and differentiation [ 12 , [14] , [15] , [16] , [17] ], thus leading to broad utilization in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Autogenous transplantation, the gold standard method for bone therapy, is limited for the lack of sources of autografts [ 7 , 8 ], besides it also has a risk of infection, nerve damage and other postoperative complications [ 9 ]. To address these challenges, researchers have focused on the development of novel biomaterials with potential in tissue engineering and regeneration to facilitate bone regeneration [ [10] , [11] , [12] , [13] ]. Among synthetic biomaterials, hydrogels consisting of natural or synthetic polymers that exhibit excellent mechanical properties and biocompatibility are ideal scaffolds to emulate extracellular matrices for cell proliferation and differentiation [ 12 , [14] , [15] , [16] , [17] ], thus leading to broad utilization in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…PDLGA, such as other biomaterials used for biomedical purposes, should be nontoxic (glycolic and lactic acids are easy metabolized by the body) [ 37 ], bioresorbable, able to attach the cells, promote their proliferation and differentiation, and also degrade according to physiological rates [ 38 , 39 ]. Thus, it is crucial to estimate the degree and rate of degradation of this type of materials, in order to apply the proper material depending of the application.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that HCP is an artificial composite material that promotes osteogenesis by osteoinduction and osteoconduction, and it has been considered as one of the most prospective materials for tissue engineering . Wang F et al demonstrated that the HCP scaffolds were the most suitable for adhesion, proliferation, and osteogenic differentiation of human umbilical cord mesenchymal stem cells in nude mouse subcutaneous implantation.…”
Section: Discussionmentioning
confidence: 99%